Storage Stability of Minced Chicken Meat and Pork at Ambient Temperature - Rushitha, K; Sudheer, K; Naveen , Z; Chakravarthi , M Kalyana (Journal of Meat Science, 2024)
With the increase in human population, the demand for food has also risen up. The food processing outlets mostly handle minced meat at ambient temperatures to cater the consumers choice. Identifying the exact spoilage time can safeguard the health of the consumer and also minimize the losses to the food handlers. With this outlook a work was designed in order to study the spoilage pattern of chicken meat and pork at ambient temperature. The chicken meat and pork were procured hygienically from scientifically slaughtered poultry birds and pigs, and then minced using a mincer with a pore size of 10mm. The minced chicken meat and pork were analyzed for physico-chemical, microbiological and sensory parameters at ambient temperature for hourly interval. The results indicated a significant increase in pH, tyrosine value, TBARS values, weight loss and microbial profiles (Total plate count, Yeast and mould count, and Coliform count), and also a significant decrease in ERV and sensory (appearance, texture, odour and overall acceptability) scores of both minced chicken meat and pork with increase in storage period. Hence, it can be concluded that the shelf life of minced chicken meat and pork at ambient temperature was 3 hours and 6 hours respectively.